A Critical Review on the Book Islamic Political Philosophy in West - Mohammad Hossein Badamchi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Islamic Political Philosophy in West published by Muhsin Rezvani (at 2014) is the first book written in Persian which is presenting a comprehensive report of contemporary and especially recent western research about Farabi and Islamic political philosophy. This paper through a critical scrutiny reveals a methodological ambivalence in formation of the ideas and organization of the book, in addition to an apolitical reading of political philosophy which cause various problems in categorizing western studies of Islamic political philosophy in four groups of Historical/ Interpretative/ Critical/ Descriptive approaches. Considering the conclusion part of the book, the implicit hidden layer of formation the book seems to be the theological-ideological concern of researcher to give an apology for “Islamic Philosophy” against what he considers as orientalist attacks. This hidden agenda of the book deviates its interpretation of Leo Strauss’s reading of Alfarabi and evaluation of other Western studies of Islamic political philosophy.